PERAN PEMERINTAH DESA DALAM PROMOSI KERAJINAN GERABAH DI DESA WISATA PENAKAK KABUPATEN LOMBOK TIMUR - Lalu Moh. Nazar Fajri; M. Adib Zata Ilmam; Hamdi, Hamdi; Rohani Inta Dewi; Ririn Febrina (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Desa Masbagik Timur, also known as Penakak Village, has a long-standing reputation as the oldest village in pottery craftsmanship production in East Lombok Regency. In the past, a significant portion of the village's population relied on pottery craftsmanship as their livelihood. However, after the Bali bombing incident, pottery production experienced a decline in activity. Despite various plastic and metal products entering the market, efforts to promote pottery craftsmanship continue to be intensified by the village government, artisans, and entrepreneurs to stimulate consumer purchases and attract new customers in order to improve the community's well-being. This motivated the researcher to investigate " The Role of Village Government in Promoting Pottery Crafts in Penakak Tourism Village, East Lombok Regency." This research utilized a descriptive qualitative method, with research subjects including village government officials and pottery artisans. Data collection techniques involved interviews, observations, and documentation. The research findings indicate that: (1) The role of the village government in promoting pottery craftsmanship has been executed as effectively as possible, (2) The village government's efforts in promoting pottery craftsmanship, including organizing exhibitions and utilizing internet promotions, have proceeded smoothly, (3) Factors hindering pottery craftsmanship promotion by the village government encompass suboptimal promotion mix, low quality of human resources, limited motivation among artisans for development, and disruptions caused by natural disasters such as the COVID-19 pandemic, impeding the smooth progress of promotions.